Heaven official's blessing, manhua. Volume 6 - Moxiangtongxiu (Aloha Comics, 2025)
The thrilling finale is here! Xie Lian unravels the dark truth behind the chaos haunting Banyue, but uncovering the secrets comes at a steep cost. Now, the Crown Prince faces a deadly threat to his life. Still, His Highness stands firm: preparing a meal for his companion and listening intently to the captivating stories from the Ghost Realm.